Impact of L-carnitine in narcolepsy treatment: a systematic review on the effectiveness and safety - Cristina Salles; Maria Clara Freitas; Miguel Meira e Cruz (Sleep Science)
Introduction: Studies have shown that narcolepsy patients may present with low serum acylcarnitine levels, demonstrating a dysfunctional beta fatty acid oxidation pathway in these patients. Objective: Evaluate the therapeutic efficacy of L-carnitine as a treatment for narcolepsy patients. Methods: This study runned in form of systematic review. The terms used for the search: (“narcolepsy”[MeSH Terms] OR “narcolepsy”[All Fields]) AND (“carnitine”[MeSH Terms] OR “carnitine”[All Fields] OR “l carnitine”[All Fields]). Were included all surveys published until January 2021, with the diagnosis of narcolepsy, that performed drug treatment with I-carnitine. The clinical endpoints of interest were: excessive daytime sleepiness, dissociative REM sleep manifestations: cataplexy, sleep paralysis, hypnagogic hallucinations, and early REM sleep (REM sleep naps, SOREMP). Results: L-carnitine was found to be well-tolerated and without side effects in all surveys, at dosages ranging from 500 to 510 mg/day. Newborns did not present complications during delivery. Conclusion: This study corroborates the efficacy and good tolerability of L-carnitine therapy as a treatment for patients with narcolepsy, including during pregnancy.